2014
DOI: 10.3390/v6052052
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Adenovirus in Chinstrap Penguins (Pygoscelis antarctica) in Antarctica

Abstract: Adenoviruses (family Adenoviridae) infect various organ systems and cause diseases in a wide range of host species. In this study, we examined multiple tissues from Chinstrap penguins (Pygoscelis antarctica), collected in Antarctica during 2009 and 2010, for the presence of novel adenoviruses by PCR. Analysis of a 855-bp region of the hexon gene of a newly identified adenovirus, designated Chinstrap penguin adenovirus 1 (CSPAdV-1), showed nucleotide (amino acid) sequence identity of 71.8% (65.5%) with South Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…The superiority of this PCR in detecting AdVs belonging to different genera has been documented in numerous cases in the past decade. It was originally designed for the recognition of novel atadenovirues in lizards, but its sensitivity and robustness allowed the discovery of many new aviadenoviruses (Wellehan et al, 2005;Bodewes et al, 2013), siadenoviruses (Katoh et al, 2009;Wellehan et al, 2009;Kovács et al, 2010;Park et al, 2012;Ballmann and Vidovszky, 2013;Joseph et al, 2014;Lee et al, 2014), atadenoviruses (Szirovicza et al, 2016) and mastadenoviruses (Vidovszky et al, 2015) in a wide range of hosts. Even the members of a hitherto unknown genus (with the proposed name Testadenovirus) could be detected (Doszpoly et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superiority of this PCR in detecting AdVs belonging to different genera has been documented in numerous cases in the past decade. It was originally designed for the recognition of novel atadenovirues in lizards, but its sensitivity and robustness allowed the discovery of many new aviadenoviruses (Wellehan et al, 2005;Bodewes et al, 2013), siadenoviruses (Katoh et al, 2009;Wellehan et al, 2009;Kovács et al, 2010;Park et al, 2012;Ballmann and Vidovszky, 2013;Joseph et al, 2014;Lee et al, 2014), atadenoviruses (Szirovicza et al, 2016) and mastadenoviruses (Vidovszky et al, 2015) in a wide range of hosts. Even the members of a hitherto unknown genus (with the proposed name Testadenovirus) could be detected (Doszpoly et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The first members of the genus Siadenovirus were discovered in poultry showing different signs of serious disease (Smyth and McNulty, 2008), as well as in a frog (Davison et al, 2000). While the number of siadenoviruses detected in a wide range of birds is increasing (Zsivanovits et al, 2006;Kovács et al, 2010;Park et al, 2012;Lee et al, 2014), there are only two approved members of the genus Atadenovirus known to be capable of infecting birds. Pigeons have not been found to harbour AdVs from any of these two genera until now.…”
mentioning
confidence: 99%
“…However, the first adenoviruses from Antarctic animals have only recently been identified among South Polar skua (Skua siadenovirus A) (Park et al, 2012), as well as chinstrap, Adélie and gentoo penguins (Penguin siadenovirus A) (Table 2, Fig. 1) (Lee et al, 2014;Lee et al, 2016). This provides important insight to monitoring penguin health in Antarctica, as adenoviruses have been known to cause severe disease among animals.…”
Section: Adenoviridaementioning
confidence: 97%
“…Most of the early studies have relied on serological assays for identifying putative paramyxoviruses, orthomyxoviruses, flavirviruses and birnaviruses in wild penguin populations (Alexander et al, 1989;Austin & Webster, 1993;Gardner et al, 1997;Miller et al, 2010;Morgan et al, , 1985Smith et al, 2008;Thomazelli et al, 2010) and herpesviruses and togaviruses in captive individuals (Kincaid et al, 1988;Tuttle et al, 2005). A handful of recent studies have identified some of the viruses (avipoxviruses, Newcastle disease viruses, adenovirus, avian influenza virus and papillomavirus) at a molecular level (Carulei et al, 2009;Hurt et al, 2014;Kane et al, 2012;Lee et al, 2014;Thomazelli et al, 2010;Varsani et al, 2014).…”
mentioning
confidence: 99%
“…To the best of our knowledge, this is one of the five genomes of viruses associated with Antarctic animals to be characterized to date; previously identified viral genomes include those of a P. adeliae papillomavirus and an avian influenza virus subtype H11N2 from Adélie penguins (Hurt et al, 2014;Varsani et al, 2014) and adenoviruses from South Polar skuas and chinstrap penguins (Pygoscelis antarctica) (Lee et al, 2014;Park et al, 2012). This highlights the poor knowledge of viruses associated with Antarctic animals.…”
mentioning
confidence: 99%